Inflammatory Markers and Risk of Hip Fracture in Older White Women: The Study of Osteoporotic Fractures. (September 2014) - Barbour, Kamil E; Lui, Li‐Yung; Ensrud, Kristine E; Hillier, Teresa A; LeBlanc, Erin S; Ing, Steven W; Hochberg, Marc C; Cauley, Jane A; for the Study of Osteoporotic Fractures (SOF) Research Group
Abstract Hip fractures are the most devastating consequence of osteoporosis and impact 1 in 6 white women leading to a two‐ to threefold increased mortality risk in the first year. Despite evidence of inflammatory markers in the pathogenesis of osteoporosis, few studies have examined their effect on hip fracture. To determine if high levels of inflammation increase hip fracture risk and to explore mediation pathways, a case‐cohort design nested in a cohort of 4709 white women from the Study of Osteoporotic Fractures was used. A random sample of 1171 women was selected as the subcohort (mean age 80.1 ± 4.2 years) plus the first 300 women with incident hip fracture. Inflammatory markers interleukin‐6 (IL‐6) and soluble receptors (SR) for IL‐6 (IL‐6 SR) and tumor necrosis factor (TNF SR1 and TNF SR2) were measured, and participants were followed for a median (interquartile range) of 6.3 (3.7, 6.9) years. In multivariable models, the hazard ratio (HR) of hip fracture for women in the highest inflammatory marker level (quartile 4) was 1.64 (95% confidence interval [CI], 1.09–2.48, p trend = 0.03) for IL‐6 and 2.05 (95% CI, 1.35–3.12, p trend <0.01) for TNF SR1 when compared with women in the lowest level (quartile 1). Among women with 2 and 3–4 inflammatory markers in the highest quartile, the HR of hip fracture was 1.51 (95% CI, 1.07–2.14) and 1.42 (95% CI, 0.87–2.31) compared with women with zero to one marker(s) in the highest quartile (p trend = 0.03). After individually adjusting for seven potential mediators, cystatin‐C (a biomarker of renal function) and bone mineral density (BMD) attenuated HRs among women with the highest inflammatory burden by 64% and 50%, respectively, suggesting a potential mediating role. Older white women with high inflammatory burden are at increased risk of hip fracture in part due to poor renal function and low BMD. © 2014 American Society for Bone and Mineral Research.